Diagnosis of the problems in Korean military force development systems - Kang, Chunsoo; Kim, Juchan (Journal of Advances in Military Studies, 2021)
The Republic of Korea (ROK) military has pursued development with a focus on the defense force development system since the Yulgok project, which began in the 1970s for the purpose of self-defense. Currently, the ROK defense force development system seems to be very methodical, and it determines requirements by using the joint combat development system, reflects the budget in the defense planning and management system, and manages the acquisition project in the defense acquisition system; however; it has many problems. These problems include fierce competition among the services, limited verification, ambiguous standards and references for requirements, complicated procedures and regulations, and failure to reflect the rapid changes in the security environment and science and technology in military force development. The most important issue is that the Joint Chiefs of Staff should lead the development of the forces based on the concept of joint operations; however, they are focused on only the current operation and neglect their main goals as the top military organization, such as mid- to long-term force development and military strategy. The Joint Chiefs of Staff should revise the organization, mission performance system, and regulations to properly perform the core functions of the defense organization that establishes long-term response strategies and builds response capabilities according to the changes in the security and strategic environment.